Funny bikes: a symmetrical study of urban space, vehicular units and mobility through the voyeuristic spokesperson of a video lens. Issue 1 (2nd January 2019) - Normark, Daniel; Cochoy, Franck; Hagberg, Johan
Abstract : This paper presents methodological considerations from a comparative, symmetrical video analysis of cyclist practices in Gothenburg and Toulouse. Video recording pays as much attention to the properties of bicycles as to the characteristics of people; it takes into account the pragmatic and situated dimension and, thus, allows a generalised symmetry. From there, visual methods enable us to submit the collected material to a double treatment of a quantitative analysis of observed bicycles and a qualitative ethnomethodological analysis of bike rental sequences. To better understand the logic and challenges of our method, we present it alongside an analogy with a famous film equivalent – the strategy used by the film-maker Michael Haneke in his heuristic film(s), Funny Games. Despite objectives and content that are obviously completely at odds to one another, the Funny Games film(s) and our own videos share at least five interesting features: twin films, static shots, photomontage, silent films, and rewinding.